The Role of Sperm Morphology Standards in the Laboratory Assessment of Bull Fertility in Australia - Perry, V.E.A. (Frontiers in Veterinary Science, 2021)
The lack of standardisation in the laboratory assessment of semen questions the reliability of semen analysis, and makes meaningful interpretation of these evaluations impossible (Brito 2016). We herein describe a standardisation program for morphology assessment currently in place in Australia and outline the methods used, both for the categorisation of the abnormalities, including newly described abnormalities, and those that permit standardised microscopic assessment between laboratories.